Antarctic marine ciliates under stress: superoxide dismutases from the psychrophilic Euplotes focardii are cold-active yet heat tolerant enzymes - Pischedda, P; Ramasamy, P K; Mangiagalli, M; Chiappori, F; Milanesi, L; Miceli, C; Pucciarelli, S; Lotti, M (Scientific Reports, 2018)
Oxidative stress is a particularly severe threat to Antarctic marine polar organisms because they are exposed to high dissolved oxygen and to intense UV radiation. This paper reports the features of three superoxide dismutases from the Antarctic psychrophilic ciliate Euplotes focardii that faces two environmental challenges, oxidative stress and low temperature. Two out of these are Cu,Zn superoxide dismutases (named Ef-SOD1a and Ef-SOD1b) and one belongs to the Mn-containing group (Ef-SOD2). Ef-SOD1s and Ef-SOD2 differ in their evolutionary history, expression and overall structural features. Ef-SOD1 genes are expressed at different levels, with Ef-SOD1b mRNA 20-fold higher at the ciliate optimal temperature of growth (4 °C). All Ef-SOD enzymes are active at 4 °C, consistent with the definition of cold-adapted enzymes. At the same time, they display temperatures of melting in the range 50–70 °C and retain residual activity after incubation at 65–75 °C. Supported by data of molecular dynamics simulation, we conclude that the E. focardii SODs combine cold activity, local molecular flexibility and thermo tolerance.